2020
DOI: 10.22492/ijpbs.6.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Social Skills of Turkish Students in Japan: Implications for Overcoming Academic and Social Difficulties During Cross-Cultural Transition

Abstract: he present study examines the social skills of Turkish students during their cross-cultural transition to the academic and social cultures of Japan. One of the purposes of this study is to partially fill the gap in the literature by exploring and identifying Turkish students’ social skills during their stay in Japan. Another purpose of the study is to differentiate social skills, particularly used in educational settings – such as the classroom environment – from those exhibited in other contexts. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Social and cross-cultural skills are related to human behavior in societies and cultures. Argyle (1994) argued that social skills govern human behavior in verbal and non-verbal interactions among individuals according to different cultures (Sozen et al, 2020). Because of the diversity in human behavior across cultures, a globalized society requires skills to adapt to different cultures.…”
Section: Social and Cross-cultural Skillsmentioning
confidence: 99%
“…Social and cross-cultural skills are related to human behavior in societies and cultures. Argyle (1994) argued that social skills govern human behavior in verbal and non-verbal interactions among individuals according to different cultures (Sozen et al, 2020). Because of the diversity in human behavior across cultures, a globalized society requires skills to adapt to different cultures.…”
Section: Social and Cross-cultural Skillsmentioning
confidence: 99%
“…This article adopts the method of interviews, where the author interviewed two international high school students. It is suggested that meaningful social interactions with host people can help international students acquire and develop culture-specific social skills that facilitate efficient cross-cultural interactions [7]. The interview consisted of a total of 13 questions, covering basic information such as age, grade, and gender, as well as the frequency and functions of the software they frequently use.…”
Section: Interview Introductionmentioning
confidence: 99%